Checkerboards and coase: transactions costs and efficiency in land markets - Randall K. Q. Akee (Institute for the Study of Labor (IZA), 2006)
The Coase theorem emphasizes the role transactions costs play in efficient market outcomes. We document inefficient outcomes, in the presence of a transactions cost, in southern California land markets and the corresponding transition to efficient outcomes after the transactions cost is eliminated. In the late 1800s, Palm Springs, CA was evenly divided, in a checkerboard fashion, and property rights assigned in alternating blocks to the Agua Caliente tribe and a non-Indian landowner by the US Federal government. Sales and leasing restrictions on the Agua Caliente land created a large transactions cost to development on those lands; consequently, we observe very little housing investment. Non-Indian lands provide a benchmark for efficient outcomes for the Agua Caliente lands. Once the transactions cost for Agua Caliente lands was removed, there is a convergence between American Indian-owned and non Indian-owned lands in both the number of homes constructed and the value of those homes.
urn:nbn:de:101:1-2008072406
Keywords: 330